Uso de tecnologías digitales en la enseñanza-aprendizaje de educación física para estudiantes de bachillerato en la Unidad Educativa Lauro Guerrero, 2024-2025 - Rojas Rojas, Luis Alfredo (2025)
This research study, titled The use of digital technologies in the teaching and learning of Physical Education for high school students in the national education system, aims to analyze the relationship between digital technologies and the teaching-learning process in Physical Education.The main goal is to evaluate how digital technologies can improve participation, inclusion, and teaching strategies in Physical Education, ensuring both theoretical and practical learning. The study also proposes innovative strategies using these technologies to enhance students' physical development and learning. The research was conducted with 45 high school students and one Physical Education teacher from “Unidad Educativa Lauro Guerrero Becerra”. The methodology combines different scientific methods, including surveys for students to explore how flexible technologies are, and interviews with the teacher to gain insights into the use of digital tools in education. The findings reveal a significant connection between digital technologies and the improvement of the educational process in Physical Education. These tools make learning more interactive, inclusive, and dynamic, fostering a well-rounded learning experience. As a result, the study proposes an interactive and adaptable teaching method that combines physical activity with theoretical learning about health, wellness, and skills. It incorporates gamification, virtual collaborative learning, and instant feedback to boost motivation, performance, and student evaluation. This innovative approach modernizes Physical Education, aligning it with current needs and promoting a dynamic and comprehensive educational experience. Keywords: digital technologies, teaching-learning, Physical Education, educational tools.